2020
DOI: 10.1038/s41598-020-61311-9
|View full text |Cite
|
Sign up to set email alerts
|

Autologous cord blood cell therapy for neonatal hypoxic-ischaemic encephalopathy: a pilot study for feasibility and safety

Abstract: Neonatal hypoxic-ischaemic encephalopathy (HIE) is a serious condition; many survivors develop neurological impairments, including cerebral palsy and intellectual disability. Preclinical studies show that the systemic administration of umbilical cord blood cells (UCBCs) is beneficial for neonatal HIE. We conducted a single-arm clinical study to examine the feasibility and safety of intravenous infusion of autologous UCBCs for newborns with HIE. When a neonate was born with severe asphyxia, the UCB was collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(38 citation statements)
references
References 43 publications
(50 reference statements)
1
35
0
Order By: Relevance
“…This study casts doubt upon the conclusions drawn from previous trials of IV cell therapy in neonates, though reports of detailed infusion protocols used during neonatal cell therapy are sparse. 7,23 Our group reported the protocol used in our first-in-human safety study of hAECs. 7 Six infants with established BPD were given 1 million hAECs/kg intravenously.…”
Section: Discussionmentioning
confidence: 99%
“…This study casts doubt upon the conclusions drawn from previous trials of IV cell therapy in neonates, though reports of detailed infusion protocols used during neonatal cell therapy are sparse. 7,23 Our group reported the protocol used in our first-in-human safety study of hAECs. 7 Six infants with established BPD were given 1 million hAECs/kg intravenously.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the contributions of sexual dimorphism to myelination and microglial polarization following neonatal H‐I injury warrant further study in both sexes. Cell‐specific targeting methods are also worth considering as potential therapeutic strategies; these approaches include the site‐specific delivery of D‐NAC targeting microglia, intranasal MSC treatment, and autologous cord blood cell therapy (Donega et al., 2014; Nance et al., 2015; Tsuji et al., 2020). Ideally, the advantage of intranasal administration is that patients are able to be treated locally and avoid the side effects of drugs on peripheral organs.…”
Section: Conclusion and Prospectsmentioning
confidence: 99%
“…Effects of these stem cells are due to the promotion of endogenous neurogenesis through the secretion of various growth factors, angiogenesis, and anti‐inflammatory effects, rather than differentiation of their own cells into neural cells 97 . Several clinical trials investigating the administration of UCBCs and BMSCs have shown their safety and feasibility 98–101 . However, no successful clinical method to improve neurobehavioral functions by enhancing neurogenesis has been reported.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…97 Several clinical trials investigating the administration of UCBCs and BMSCs have shown their safety and feasibility. [98][99][100][101] However, no successful clinical method to improve neurobehavioral functions by enhancing neurogenesis has been reported. Combinations of the approaches mentioned above and optimization of dosages and timing of treatment is expected to lead to promising results in neonatal patients with brain injury.…”
Section: Clinical Application Of Endogenous Nsc-derived Neural Regenementioning
confidence: 99%